2006
DOI: 10.1007/s10461-006-9103-9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cannabis Use and Sexual Risk Behavior Among Young Heterosexual Adults

Abstract: To study the association between cannabis use and frequent sexual risk behavior, we tested the hypothesis of a situational influence of cannabis use in sexual encounters using a combination of global association study and event-level analysis and examined possible mediator variables, including the personality trait of hedonism/risk preference, psychosocial stress, and HIV-related beliefs, using mediation models. The results of a computer-assisted telephone interview of a random sample of 2790 heterosexual men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
54
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 19 publications
10
54
0
5
Order By: Relevance
“…Likewise, cannabis use (among women) was found to be associated with HIV risk behaviour, which conforms with several studies. [42,44,45] This study did not find depressive symptomatology to be a predictor of HIV risk behaviour, as found in some other studies. [14,15] Further, among women, being in the fourth or more year of study was associated with HIV risk behaviour.…”
Section: Discussionsupporting
confidence: 69%
“…Likewise, cannabis use (among women) was found to be associated with HIV risk behaviour, which conforms with several studies. [42,44,45] This study did not find depressive symptomatology to be a predictor of HIV risk behaviour, as found in some other studies. [14,15] Further, among women, being in the fourth or more year of study was associated with HIV risk behaviour.…”
Section: Discussionsupporting
confidence: 69%
“…However, they were more likely to report having a cannabis use disorder, and this SUD was specifically associated with STDs in the current study, consistent with the literature on cannabis use and risky behavior. [37][38][39] In addition, African American race was a significant predictor of risk for ever having had an STD in the multivariate models, even after controlling for age, SUD, and BPD dimensional scores. Therefore, the health disparities seen in the general population appear to carry over into this psychiatric sample.…”
Section: Discussionmentioning
confidence: 87%
“…Street youth who used marijuana in a recent sexual encounter were less likely to use condoms, but those who used crack were more likely to use condoms (Bailey, Camlin, and Ennett, 1998). Marijuana use with sex was also associated with decreased condom use at a recent sexual encounter among adolescents in detention (Kingree and Betz, 2003;Kingree, Braithwaite, and Woodring, 2000;Kingree and Phan, 2002) and among MSM (Clutterbuck et al, 2001), but was unrelated to condom use among young heterosexual adults (Brodbeck, Matter, and Moggi, 2006). In a sample of female drug users, condom use at a recent sexual encounter was not significantly associated with use of alcohol, injection drugs, crack, or noninjection drugs before sex (Tortu et al, 2000), while a study of drug injectors suggested decreased condom use when both sexual partners were using crack with sex (Friedman et al, 1999).…”
Section: Introductionmentioning
confidence: 98%